2017
DOI: 10.1097/qad.0000000000001392
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions between hormonal contraceptives and antiretrovirals

Abstract: Objective:To summarize published evidence on drug interactions between hormonal contraceptives and antiretrovirals.Design:Systematic review of the published literature.Methods:We searched PubMed, POPLINE, and EMBASE for peer-reviewed publications of studies (in any language) from inception to 21 September 2015. We included studies of women using hormonal contraceptives and antiretrovirals concurrently. Outcomes of interest were effectiveness of either therapy, toxicity, or pharmacokinetics. We used standard ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 72 publications
0
70
0
1
Order By: Relevance
“…21 A recent systematic review found that the most noteworthy interactions occurred for cisgender women using NNRTIs, and particularly efavirenz, although these outcomes were predominantly pharmacokinetic in nature and assessed interactions at doses used for contraception rather than feminizing HT. 22 No studies have specifically addressed interactions between ART and the estrogen regimens/doses used for feminizing HT. Thus, there are insufficient data to fully understand the risk of DDIs between ART and HT for TW.…”
Section: Braun Et Almentioning
confidence: 99%
“…21 A recent systematic review found that the most noteworthy interactions occurred for cisgender women using NNRTIs, and particularly efavirenz, although these outcomes were predominantly pharmacokinetic in nature and assessed interactions at doses used for contraception rather than feminizing HT. 22 No studies have specifically addressed interactions between ART and the estrogen regimens/doses used for feminizing HT. Thus, there are insufficient data to fully understand the risk of DDIs between ART and HT for TW.…”
Section: Braun Et Almentioning
confidence: 99%
“…[73] There are substantial drug interactions between efavirenz and Implanon, considerably reducing drug levels of etonogestrel, the active drug in Implanon. [74][75][76] Interactions between efavirenz and Jadelle appear even more pronounced than with Implanon. [77,78] Women using an implant, who are also taking efavirenz, have higher pregnancy rates than those taking other antiretrovirals.…”
Section: Cmementioning
confidence: 99%
“…Available data therefore do not support limiting access to the implant in women taking efavirenz. [75] Moreover, the use of efavirenz is likely to be phased out over time, alleviating many of these concerns.…”
Section: Cmementioning
confidence: 99%
“…Generally, NRTIs and INSTIs are not considered significant inhibitors, inducers, or substrates of CYP450 enzymes, and, therefore, unlikely to influence hormonal contraceptive exposure [14,15]. Two recent systematic reviews on DDIs between hormonal contraceptives and antiretrovirals for women living with HIV thoroughly cover the aforementioned aspects [15,16]. In Section 3, we highlight pertinent findings for each combination of contraceptive method and antiretroviral classes.…”
Section: General Principles For Contraceptive Provisionmentioning
confidence: 99%